2000
DOI: 10.1038/sj.cgt.7700268
|View full text |Cite
|
Sign up to set email alerts
|

The expression of CD70 and CD80 by gene-modified tumor cells induces an antitumor response depending on the MHC status

Abstract: The expression of costimulatory molecules such as CD70 or CD80 by gene -modified tumor cells has been shown to enhance the antitumor immune response based mainly on T lymphocytes. However, most human tumors show defects of major histocompatibility complex ( MHC ) expression, preventing them from being recognized by MHC -restricted T cells. To investigate if coexpression of CD70 and CD80 costimulatory molecules induces comparable antitumor responses in low and high MHCexpressing tumor cells, we used two low imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…In addition, two separate groups recently reported that coexpression of CD70 and B7-1 on tumor cells enhances antitumor immune responses (63,64). Our data clearly demonstrate that CD27-CD70 is also a critical costimulatory pathway for CD8 ϩ T cell-mediated alloimmune responses.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, two separate groups recently reported that coexpression of CD70 and B7-1 on tumor cells enhances antitumor immune responses (63,64). Our data clearly demonstrate that CD27-CD70 is also a critical costimulatory pathway for CD8 ϩ T cell-mediated alloimmune responses.…”
Section: Discussionsupporting
confidence: 71%
“…It is the capacity to trigger expansion of effector T cells by which CD70 recommends itself as a highly relevant costimulatory signal, as documented by a number of murine models for cancer vaccines (42)(43)(44). Our own data showed that in leukemic mice, CD70 expressed by the vaccine cells does indeed induce a potent antileukemic response, which is predominantly mediated by CD8 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, high expression of CD70 has been found in malignant lymphomas and nasopharyngeal tumors (18) and in all examined clear cell tumors, whereas no expression occurred in the related normal epithelial cells.…”
Section: Inhibitors (Nevirapine Lane 4; Efavirenz Lane 5) Negativementioning
confidence: 94%